Renal impairment as a risk factor for chemotherapy induced neutropenia in the treatment of trifluridine/thymidine phosphorylase inhibitor plus bevacizumab - Masatsune Shibutani; Hideki Tanda; Hiroaki Kasashima; Tatsunari Fukuoka; Shinichiro Kashiwagi; Kiyoshi Maeda (Scientific Reports)
Abstract Although the phase III SUNLIGHT trial has demonstrated the survival benefit of the addition of bevacizumab (Bmab) to trifluridine/thymidine phosphorylase inhibitor (FTD/TPI), neutropenia, which frequently occurs during FDT/TPI + Bmab therapy, is a concern for clinicians. As TPI is excreted by the kidneys, the risk of adverse events is likely to be high in patients with an impaired renal function. This study aimed to investigate the relationship between renal impairment and the incidence of chemotherapy-induced neutropenia during FTD/TPI + Bmab therapy using real-world data. We retrospectively reviewed the medical records of 69 patients with metastatic colorectal cancer (mCRC) who were treated with FTD/TPI + Bmab for more than 28 days. Patients with renal impairment with an eGFR of 30–44 mL/min/1.73 m2 were defined as the G3b group. Seven patients (10.1%) were classified into the G3b group. Patients in the G3b group had an approximately 24% higher incidence of grade ≥ 3 neutropenia in comparison to others (71.4% vs. 46.8%), and the incidence of grade 4 neutropenia in the G3b group was significantly higher than that in others (42.9% vs. 9.7%, p = 0.042). The G3b group frequently developed grade ≥ 3 neutropenia within 30 days of the initiation of FTD/TPI + Bmab therapy. However, the duration required for neutrophil count to recover to ≥ 1500/mm3 and the treatment effects of the G3b group were comparable to those observed in other patients. Clinicians should pay extra attention to patients with a decreased renal function who are treated with FTD/TPI + Bmab therapy, but no special measures are required for patients with an eGFR ≥ 30 mL/min/1.73 m2 as no marked differences were observed in neutrophil count recovery.